Thrombospondin-1 Silencing Down-Regulates Integrin Expression Levels in Human Anaplastic Thyroid Cancer Cells with BRAFV600E: New Insights in the Host Tissue Adaptation and Homeostasis of Tumor Microenvironment - Duquette, Mark; Sadow, Peter M.; Lawler, Jack; Nucera, Carmelo (Frontiers in Endocrinology, 2013)
Background and Rationale: Anaplastic thyroid cancer (ATC) is characterized by pleomorphic cells, has a poor prognosis, is highly devastating disease, and is not curable. No reliable biomarkers of metastatic potential, helpful for early diagnosis of ATC and therapeutic response have been found yet. Thrombospondin-1 (TSP-1) plays a fundamental role in cancer progression by regulating cell stromal cross-talk in the tumor microenvironment. Goals: Our goal was to understand whether TSP-1 could affect protein levels of its integrin receptors (e.g., ITGα3, α6, and β1) and cell morphology in BRAFV600E-ATC cells in vitro and in vivo. Experimental Design: Anaplastic thyroid cancer-derived cell cultures and western blotting were used to assess integrin protein expression upon TSP-1 silencing. Immunohistochemistry was performed on orthotopic primary human ATC and metastatic ATC in lung tissue to compare TSP-1 and integrin protein expression levels. Results: TSP-1 knock-down down-regulates ITGα3, α6, and β1 in BRAFV600E-human ATC cells. BRAFV600E-ATC cells with TSP-1 knock-down were rounded compared to control cells, which displayed a spread morphology. TSP-1 knock-down also reduced TSP-1, ITGα3, α6, and β1 protein expression levels in vivo in the ATC microenvironment, which is enriched in stromal and inflammatory cells. Conclusion: TSP-1 silencing causes changes in ITG levels and ATC cell morphology. The assessment of TSP-1 and ITG levels might contribute to earlier metastatic potential of BRAFV600E-positive aggressive thyroid cancers, and allow improved patient selection for clinical trials.